Pengembangan Religiusitas Siswa di SMA PGRI 4 Banjarmasin: Development of Student Religiosity at SMA PGRI 4 Banjarmasin - Salis, M. Rizkoni (Rumah Riset Publisher, 2024)
This research aims to describe the development of student religiosity in several activities that take place at SMA PGRI 4 Banjarmasin. This research method uses a descriptive qualitative approach with data collection techniques in the form of interviews and observations. Observations were used to determine the existence of the vision, mission and goals of SMA PGRI 4 Banjarmasin, while interviews were conducted to determine the ongoing development of student religiosity in several activities. The data analysis is descriptive using a literature review using journals or books so that this research is structured systematically and can be understood with appropriate explanations. The results of this research show efforts to develop student religiosity at SMA PGRI 4 Banjarmasin which includes several activities, namely: Congregational Dhuha Prayer every school day in the prayer room, Reading the Asmaul Husna after carrying out congregational Dhuha prayers, Congregational Dhuha Prayer, Jum'ah at Taqwa which is held twice a month every Friday morning before the teaching and learning process in the school field and KSI (Islamic Study Group) which is held every Wednesday at 14.30-16.00 WITA.